The Value-Congruence Model of Memory for Emotional Experiences: An Explanation for Cultural Differences in Emotional Self-Reports - OISHI, Shigehiro (Institutional Knowledge at Singapore Management University, 2007)
In 3 studies, the authors found support for the value-congruence model that accounts for cultural variations in memory for emotional experiences. In Study 1, the authors found that in the made-in-the-U.S. scenario condition, European Americans were more accurate than were Asian Americans in their retrospective frequency judgments of emotions. However, in the made-in-Japan scenario condition, European Americans were less accurate than were Asian Americans. In Study 2, the authors demonstrated that value orientation mediates the Culture X Type of Event congruence effect. In Study 3 (a daily event sampling study), the authors showed that the congruence effect was explained by the importance of parental approval. In sum, emotional events congruent with personal values remain in memory longer and influence retrospective frequency judgments of emotion more than do incongruent events.